About the model of separation of powers in the Republic of Kazakhstan - Akhmetova, N.S.; Mausymbayeva, А.А. (KSU publ., 2015)
In this article we analyzed all kinds of organization of state power, which in legal science taken to reduce to a few typological models, depending on the form of government. Within the framework of the modern legal integration the features of that models of separation of powers, which are implemented in the practice of developed countries in legal terms are disclosed that can detect a specific historical identity of each of these models. Detailed analysis of types of organization of the state power in terms of their membership of a particular model of separation of powers is theoretically possible to determine the potential and practically realized model of separation of powers and form of manifestation (implementation) in the Republic of Kazakhstan.
Keywords: model of separation of powers; «checks and balances»; the principle of separation of powers; form of government branch; state power